Efficacy of Vamana Karma in the Management of Kshetra Dushti Janya Bandhyatva (Uterine Fibroid) (AYUSHDHARA, 2024)
Fibroids, one of the major reason for infertility are present in 5- 10% of infertile patient. Depending on the location in the uterus, fibroid prevent conception by causing difficulty in sperm ascent, impaired sperm transport and hindering the nidation of fertilized ovum. Thus, fibroids have been implicated in infertility as well as pregnancy loss. Hereby, we are reporting a case of a 31year-old married female who visited the OPD of the National Institute of Ayurveda, Jaipur. She came with complaints of being unable to conceive for 1 year. Ultrasonography dated July 13, 2022, suggested a bulky uterus with intramural fibroid (85 × 65 mm). On the basis of these clinical presentations and USG findings, the patient was diagnosed with infertility due to a uterine fibroid correlated with Kshetra dushti janya Bandhyatva. Vamana karma was conducted for the elimination of Kapha Dosha. After Vamana karma, she missed her period. Her UPT was performed on March 22, 2023, which was found positive. Uneventfully, the patient had delivered a live female child weighing 2.5 kg on 1/11/2023 by LSCS under SA. Vamana karma is beneficial in the management of Kshetra dushti janya Bandhyatva (infertility due to a uterine fibroid).